Survey of Access to GastroEnterology in Canada: The SAGE Wait Times Program - Desmond Leddin; Ronald J Bridges; David G Morgan; Carlo Fallone; Craig Render; Victor Plourde; Jim Gray; Connie Switzer; Jim McHattie; Harminder Singh; Eric Walli; Iain Murray; et al. (Canadian Journal of Gastroenterology)
BACKGROUND: Assessment of current wait times for specialist health services in Canada is a key method that can assist government and health care providers to plan wisely for future health needs. These data are not readily available. A method to capture wait time data at the time of consultation or procedure has been developed, which should be applicable to other specialist groups and also allows for assessment of wait time trends over intervals of years.